Iustinianos – der neue Augustus? Adoption, Name und Propaganda eines künftigen Kaisers - Ján Bakyta (Acta Universitatis Carolinae: Philologica, 2017)
This is a reappraisal of the evidence for the adoption of the later emperor Justinian by his uncle Justin, which has been questioned by Noethlichs (2001). Even though Justinianʼs references to Justin as his ʻfatherʼ are not conclusive, the epigram Anth. Gr. I, 97 can be evaluated as a reliable positive indication. The name ʻJustinianʼ is the original name of the emperor and has nothing to do with the adoption, whereas the names ʻPetrusʼ and ʻSabbatiusʼ as attested in the consular diptychs are secondary names, the former perhaps being a model for the subsequent fashion of devotional cognomina. Finally, the related issues of possible propaganda by Justinian (his comparison to Augustus adopted by Caesar) and its reception (by Procopius or John the Lydian) are discussed.